Effect of varying carbon microstructures on the ion storage behavior of dual carbon lithium-ion capacitor. (20th June 2023) - Bhattacharjee, Udita; Gautam, Abhay; Martha, Surendra K.
Highlights: Carbons with micron-sized channels and mesopores facilitate optimum Li-ion storage. Carbons with unique microstructure deliver 290 mAh g -1 till 1000 cycles at 1 a g −1 . Activated carbon from agrowaste delivers 118 f g −1, retain ∼76% till 5000 cycles. The as-assembled LIC delivers energy of ∼120 Wh kg −1 and power of 20.7 kW kg −1 . The mechanistic control over ion storage behavior of the LIC full cell is elucidated. Abstract: Dual carbon lithium-ion capacitors (LICs) are the next-generation hybrid energy storage devices that aim towards energy-power balanced applications. Thus, tuning the properties of the carbon electrode materials is a crucial step toward optimizing the device's performance. Herein, the effect of change in the microstructure of the carbon electrodes on the ion storage capacity and their consequent energy-power manifestation is investigated. The optimized carbonaceous anode calcined at 700 ⁰C delivers 290 mAh g −1 capacity after 1000 cycles at 1 A g −1 . This superiority in performance is attributed to the formation of micron-size channels and mesopores for better ion transport and storage. In contrast, the activated carbon cathode delivers a capacitance of 118 F g −1 and retains 76% at the end of 5000 cycles. The LIC full cell with these electrode materials provides maximum energy of 120 Wh kg −1, a maximum power density of 20.7 kW kg −1 and cycles till 9000 cycles with ∼67% capacitance retention. The mechanistic control over the deliverable ion storage capacity is also analyzed for the LIC full cell. Furthermore, the lighting demonstration, self-discharge studies, leakage current, and electrochemical impedance are recorded to elucidate the practical feasibility and performance degradation mechanism of the coin-cell device. Graphical abstract: Image, graphical abstract